Macular morphological prognostic factors of myopic foveoschisis with foveal detachment - Wu, Mengai; Chen, Lifeng; Fan, Yuanyuan; Lin, Li; Wang, Zhijie; Yu, Guanshun; Wu, Xinyue; Lu, Fan; Zheng, Bin (Frontiers in Medicine, 2025)
PurposeTo evaluate the optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) parameters as a prognostic indicator of visual outcome in patients with myopic foveoschisis (MF) and foveal detachment (FD).MethodsTwenty-three individuals with MF and FD and undergoing vitrectomy participated in this study. Preoperative OCT parameters were obtained, including central foveal thickness (CFT), foveal detachment thickness (FDT), foveoschisis thickness (FST), and subfoveal choroidal thickness (SCT). Preoperative optical coherence tomography angiography (OCTA) images were assessed to measure macular vascular parameters in both superficial capillary plexus (SCP) and deep capillary plexus (DCP). En-face OCTA images was also employed to determine the area and perimeter of the ellipsoid zone (EZ) fracture. Microperimetry was performed to evaluate macular sensitivity (MS) covering the central 20°, 10°, 2° field centered at fovea.ResultsThe best corrected visual acuity (BCVA) improved significantly six months after surgery. When comparing groups based on postoperative BCVA, those with BCVA ≥0.5 had a substantially lower FD height and a higher vessel density (VD) in the SCP than those with BCVA <0.5. Preoperative BCVA demonstrated significant correlations with CFT, the EZ disruption area, and the EZ disruption perimeter. Additionally, preoperative 20° MS, 10° MS, and 2° MS were separately correlated with SCT, whole DCP VD, parafoveal VD, as well as the EZ disruption area and perimeter. Multiple linear regression analysis revealed that postoperative BCVA at six months was significantly associated with preoperative BCVA and preoperative whole SCP VD.ConclusionOur study highlights that in addition to preoperative visual acuity, OCTA may be a useful additional prognostic factor for predicting visual outcomes in patients with MF and FD after vitrectomy.